Ionospheric signatures of gravity waves produced by the 2004 Sumatra and 2011 Tohoku tsunamis: A modeling study. Issue 1 (24th January 2017) - Yu, Yonghui; Wang, Wenqing; Hickey, Michael P.
Abstract: Ionospheric fluctuations inferred from observations of total electron content have previously been attributed to tsunamis and have confirmed the strong coupling between Earth's ocean and ionosphere via atmospheric gravity waves (AGWs). To further advance our understanding of this wave coupling process we employ a linear full‐wave model and a nonlinear time‐dependent model to examine the ionospheric response to the AGW perturbations induced by the 2004 Sumatra and the 2011 Tohoku tsunamis. In the 2004 case, our modeling analyses reveal that one component of the propagating AGWs becomes dynamically unstable in the E ‐region ionosphere at a range exceeding 2000 km in a direction 340° clockwise from north. Another component becomes convectively unstable in the E ‐region ionosphere at a range exceeding 700 km in a direction 250° clockwise from north. In the 2011 case, a significant enhancement in the ionospheric disturbance occurs in a direction northwest from the epicenter about 1 h following the tsunami onset, in general agreement with observations. Our simulations also indicate that the AGW propagating toward the southeast is responsible for a traveling ionospheric disturbance that remains of an observable amplitude for over 4 h during which time it propagates horizontally almost 4000 km. Key Points: A 2‐D nonlinear time‐dependent model displays azimuthally anisotropic gravity waves driven by tsunamis shown in TEC at ionospheric heights Incomplete ducting conditions may cast doubt upon a long‐range propagating gravity wave afar off the epicenter in the 2004 Sumatra event Long‐range gravity wave propagation may have been overlooked in the 2011 Tohoku event owning to sparse GPS receivers in the deep Pacific